2023
DOI: 10.1111/jace.19144
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐driven phase transition and energy conversion in ferroelectrics: Principles, materials, and applications

Abstract: The pressure‐driven explosive energy‐conversion (EEC) effect of ferroelectric (FE) materials has been extensively studied in scientific research and high‐tech applications owing to its high pulse‐power output capability. The fundamental principle of this effect is pressure‐driven phase transition and depolarization in FE materials, accompanied by discharging behavior from the charge release upon pressure loading. Pb(Zr,Ti)O3 has been an excellent example of a materials exhibiting these properties. However, rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 126 publications
(381 reference statements)
0
3
0
Order By: Relevance
“…Xie et al found that the pressure-driven explosive energy-conversion (EEC) effect of ferroelectric (FE) materials has been extensively studied in scientific research and high-tech applications because of its high pulse-power output capability. 48 This outcome shows great promise for the advancement of the next-generation energy conversion devices. Ferroelectric sensors can also benefit from the application of pressure, as it can improve both sensitivity and responsiveness.…”
Section: Introductionmentioning
confidence: 94%
“…Xie et al found that the pressure-driven explosive energy-conversion (EEC) effect of ferroelectric (FE) materials has been extensively studied in scientific research and high-tech applications because of its high pulse-power output capability. 48 This outcome shows great promise for the advancement of the next-generation energy conversion devices. Ferroelectric sensors can also benefit from the application of pressure, as it can improve both sensitivity and responsiveness.…”
Section: Introductionmentioning
confidence: 94%
“…4,5 Ferroelectric materials play a significant role in this area because of their reorientable ionic polarization, high electric charge density, extra-long storage life, and rapid response under adiabatic compression. 6,7 Shock compression drives the poled ferroelectric materials with oriented domains to be aligned in a random orientation, at which pressure-driven phase transition generates a sharp current/voltage pulse with megawatts of electric power in a short period time (∼μs). 7−9 The mainstream strategy still focuses on constructing the phase boundary from order to disorder through element doping and domain engineering in the ferroelectric materials matrix, including antiferroelectric state and relaxor-ferroelectric state.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This has led to a booming development of electrochemical cells, thermal cells, and electrochemical capacitors, which are widely applied to power autonomous electrical systems. However, these energy storage devices cannot meet the requirement of high output voltage, high current, and megawatt power levels for brief intervals of time in pulsed power energy conversion. In the field of pulse power energy conversion, stemming from research on nuclear fusion, it has become a critical technique and has been employed in applications such as mining engineering, mineral, gas and oil explorations, geology-prospecting system, and remote power supplies. , Ferroelectric materials play a significant role in this area because of their reorientable ionic polarization, high electric charge density, extra-long storage life, and rapid response under adiabatic compression. , Shock compression drives the poled ferroelectric materials with oriented domains to be aligned in a random orientation, at which pressure-driven phase transition generates a sharp current/voltage pulse with megawatts of electric power in a short period time (∼μs). The mainstream strategy still focuses on constructing the phase boundary from order to disorder through element doping and domain engineering in the ferroelectric materials matrix, including antiferroelectric state and relaxor-ferroelectric state. For example, the ∼2 mol % Nb-doped Pb­(Zr 0.95 Ti 0.05 )­O 3 (PZT95/5), considered to be a suitable candidate in energy conversion, involves the FE state to AFE state with increasing Zr elements, while the evolution from the FE to RFE state is realized via the introduction of NaNbO 3 in the (Bi,Na)­TiO 3 -based system. , A strategy based on ferroelectric materials inevitably limits candidates employed in pulse power technology.…”
Section: Introductionmentioning
confidence: 99%